2018
DOI: 10.1515/cipms-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in murine liver following HSV infection and stroke

Abstract: The study of herpetic infection is a topical problem. Although the peculiarities and consequences of acute HSV-I infection in the brain are quite well-studied, little is known about the damage to other organs which are not a source of latent HSV-I infection, the liver in particular. The current study is aimed at determining the ultrastructural changes in murine liver following HSV infection and stroke. Liver samples obtained from four groups of animals were studied: 1) intact mice; 2) mice with stroke; 3) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is currently widely recognized that any viral infection that damages endothelial cells of blood vessels can be reliably associated with the risk of vascular disease [7]. Biochemical analysis revealed that content of free and esterified cholesterol was higherin the aortic tissue specimens of CMV-infected animals with normocholesterolemia than in the models of non-infected animals.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently widely recognized that any viral infection that damages endothelial cells of blood vessels can be reliably associated with the risk of vascular disease [7]. Biochemical analysis revealed that content of free and esterified cholesterol was higherin the aortic tissue specimens of CMV-infected animals with normocholesterolemia than in the models of non-infected animals.…”
Section: Introductionmentioning
confidence: 99%